2009
DOI: 10.3390/sym1020106
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Morphological Symmetry and Immune Response in Wild-Caught Adult Bush-Crickets

Abstract: Despite interest in the relationship between fluctuating asymmetry (FA), immune response and ecological factors in insects, little data are available from wild populations. In this study we measured FA and immune response in 370 wild-caught male bush-crickets, Metrioptera roeseli, from 20 experimentally introduced populations in southern-central Sweden. Individuals with more-symmetric wings had a higher immune response as measured by the cellular encapsulation of a surgically-implanted nylon monofilament. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The results of composite (FA) indicated that feeding treatments did not affect wing angels in worker bees, but it has an effect on veins distance, as feeding with sugar cane caused significant higher (FA) than with feeding with honey. In this study we investigate the influence of artificial feeding in comparison to honey-fed colonies on the degree of symmetry between right and left wing of honeybees, as many researches established that the use of wings seems to be effective in measuring developmental instability in many insects (Parsons and Hoffmann 1991;Imasheva et al 1997;De Block and Stoks 2007;Berggren and Low 2009;Mazeed 2012;Mazeed, et al 2015).…”
Section: Fluctuating Asymmetry (Fa)mentioning
confidence: 99%
“…The results of composite (FA) indicated that feeding treatments did not affect wing angels in worker bees, but it has an effect on veins distance, as feeding with sugar cane caused significant higher (FA) than with feeding with honey. In this study we investigate the influence of artificial feeding in comparison to honey-fed colonies on the degree of symmetry between right and left wing of honeybees, as many researches established that the use of wings seems to be effective in measuring developmental instability in many insects (Parsons and Hoffmann 1991;Imasheva et al 1997;De Block and Stoks 2007;Berggren and Low 2009;Mazeed 2012;Mazeed, et al 2015).…”
Section: Fluctuating Asymmetry (Fa)mentioning
confidence: 99%
“…In this study I compare the variation in immune response toward a novel antigen from wild-caught bush-crickets in order to answer if the magnitude of the immune response (i.e., cellular encapsulation and melanization) is correlated with the color morph of the individual. To do this, I used a standard technique for measuring immune response in insects -the 'artificial parasite' -which consists of implanting a novel antigen (often a nylon monofilament) into the animal's hemocoele and quantifying the encapsulation response to this antigen (Allander & Schmid-Hempel, 2000;Rantala et al, 2000;Siva-Jothy, 2000;Civantos et al, 2005;Berggren & Low, 2009). This method is a very good measure of the individual's resistance against real pathogens and parasites (Rantala & Roff, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Roesel's bush‐cricket ( Metrioptera roeseli , Hagenbach) is a good candidate for studying relationships between color morphology and immune function because individuals develop as either a green or brown color morph (Marshall & Haes, 1988). Also, the history and environmental variables influencing many bush‐cricket populations in central‐southern Sweden (i.e., the study area) are well known (Berggren, 2001, 2005), allowing potentially confounding factors such as the size of the establishing population, landscape connectivity and patch size to be accounted for (Berggren, 2009; Berggren & Low, 2009). In this study I compare the variation in immune response toward a novel antigen from wild‐caught bush‐crickets in order to answer if the magnitude of the immune response (i.e., cellular encapsulation and melanization) is correlated with the color morph of the individual.…”
Section: Introductionmentioning
confidence: 99%